Comprehensive investigation and modeling of pitting corrosion effects on mechanical properties and fatigue performance of steel wires - XuanRui Yu; ZhiTao Yan; GaoFeng Zhang; JiaWei Liu (Case Studies in Construction Materials, 2024)
Steel wires are widely employed in structural engineering due to their robust strength. However, the emergence of pitting corrosion significantly impacts their capacity, fatigue performance, and mechanical traits, with no specific codes addressing this issue. To assess the load-bearing capacity of corroded steel wires, predict their remaining fatigue life, and analyze failure modes, a comprehensive physical test was conducted. Mechanical evaluations of corroded wires were followed by 3D scanning to analyze corrosion attributes and fracture surface morphology. Using fuzzy reliability theory, a model estimated wire capacity under varying corrosion degrees. Subsequent fatigue testing explored performance and developed a predictive residual life model. Investigation results revealed a rapid and gradual decrease in capacity's reliability coefficient. Corroded wire fracture morphologies were classified as typical and multi-source cracks, including subtypes like cracks expanding in the same plane and step-like fractures. All wire types exhibited a cracking threshold exceeding 5.6 MPa·m1/2, with fracture intensity declining as corrosion severity increased. Notably, the model better suited slightly corroded wires, showing up to 30.93 % relative error for severely corroded wires. Enhancing accuracy for the latter entails considering additional factors to refine the model.